Risk Factors of Vitamin D Deficiency Associated with Dental Caries among School-Aged Children of District Peshawar - Ahad, Eidul; Shah, Said Muhammad Usman; Waqas, Hira; Ullah, Shakir; Saeed, Usman; Rahman, Muhammad Iqbal Khan; Ali, Haidar (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Vitamin D deficiency and dental cavities are global issues. Thus, the purpose of the study is to investigate how dental caries in school-age children from the Peshawar district is affected by vitamin D insufficiency. The study included 1600 kids ranging in age from 4 to 15 years old. To obtain samples, a methodical random sampling procedure was used. In the current study, 1600 samples were calculated to investigate vitamin D deficiency in children enrolled in school. Men were found to have a significant percentage of vitamin D insufficiency (22.5%), but female had a relatively low ratio (12.5%). Male students made up 220 (27.5%) of the school-age population, while female students made up 100 (12.5%). Both genders had significant rates of insufficiency. Age-appropriate investigation. Male students made up 220 (27.5%) of the school-age population, while female students made up 100 (12.5%). Both genders had significant rates of inadequacy. The investigation of vitamin D deficiency according to age reveals that very low frequency was found in the low aged group (4–7 years) 80 (10%), similarly low frequency was found in the 8–11 years group 120 (15%), and very high frequency was found in the 12–15 years group 160 (20%). According to the data broken down by residency, children living in urban areas had a high frequency ratio of 160(20%) compared to 120(15%) for children living in rural areas. Long-term health effects are associated with the growing issue of vitamin D insufficiency and its relationship to school-age children's intellectual performance. The current investigation demonstrated the connection between investigation of vitamin D deficiency according to age, gender, and socioeconomic position.